P110 Evaluation of trajectories in maternal mental health according to food security status: combined analysis of routine and cohort data. (13th September 2016) - Uphoff, N; Power, MS; Pickett, K
Abstract : Background: Literature from Canada and the United States indicates that household food insecurity is associated with poorer mental health, and chronic mental health conditions increase the odds of household food insecurity, independent of household socio-demographic characteristics. However, there is no published work on the longitudinal relationship between mental health and food insecurity in the UK. The objective of this paper was to assess the mental health trajectories of women who report food insecurity compared to those who report no food insecurity around 12 months after giving birth. Methods: We analysed linked data from three sources: the Born in Bradford (BiB) baseline questionnaire, data from the BiB1000 study, and GP records. BiB is a birth cohort that examines the impact of environmental, psychological and genetic factors on maternal and child health. BiB1000 is a nested cohort of BiB with 1735 mothers, aimed at identifying risk factors for obesity. The food insecurity questionnaire, derived from the USDA Food Security Survey 1995, was completed when babies were approximately 12 months old (N = 1297). Primary care records were matched to BiB data using NHS numbers (90.8% matched), and CMD was defined according to a standardised method. We calculated incidence rates of CMD per 1000 Patient Years At Risk (PYAR) among food secure compared to food insecure women in ten six-month periods. We used Poisson regression to calculate Incidence Ratio Ratios (IRR) adjusted for ethnicity, age of the mother, partner's occupation and exposure. Results: 22.1% of the sample classified as food insecure, and the incidence rate of CMD ranged from 29 to 118 per 1000 PYAR for the food secure group compared to 57 to 167 per 1000 PYAR for the food insecure group, with the lowest rates found prenatally. Incidence rates of CMD were higher for food insecure compared to food secure women in all periods. Adjusted IRRs suggest increased vulnerability both prenatally (IRR 1.46, 95% CI 0.99–2.14, p = 0.055) and postnatally (IRR 1.36, 95% CI 1.06–1.73, p = 0.014). Conclusion: This study found that women who report food insecurity seem to be at higher risk of CMD during and after pregnancy. The prevention of mental illness and food insecurity involves understanding and tackling the root causes, and it appears we are currently ignoring part of the opportunities for reducing the burden of ill health and social disadvantage.